Implementation Of The Diffusion Program And Adoption Of Vasectomy Innovation In The City of Surabaya - WONO, Hilda Yunita; SUNARTO, Sunarto; RONDA, Mirza (International Journal of Environmental, Sustainability, and Social Science, 2023)
The capital city of East Java Province, Surabaya City has the densest population. This population growth rate is the task of DP3APPKB Surabaya City to overcome it and one of the programs is vasectomy. In 2013, Surabaya received an award for fostering Vasectomy groups until the acceptance rate was high, but after that the number of acceptors continued to decline drastically until now. The purpose of this study is to look at the implementation of the vasectomy innovation diffusion and adoption program in Surabaya City. This research was conducted using a qualitative approach in order to get in-depth results from various perspectives. It was found that complexity, side effects and cost are not constraints, vasectomy diffusion channels are effective, and the added value offered is diverse. These can be further emphasized by DP3APPKB in running the next Vasectomy program.